1987
DOI: 10.1017/s0022112087001848
|View full text |Cite
|
Sign up to set email alerts
|

A bifurcation study of laminar flow in a curved tube of rectangular cross-section

Abstract: The spiralling flow within a curved tube of rectangular cross-section normally forms two distinct cells in the plane of the cross-section, but a transition to a different, four-cell flow is known to occur at a critical value of the axial pressure gradient. This paper shows that, for a square cross-section, the transition is a result of a complex structure of multiple, symmetric and asymmetric solutions. The structure is revealed by solving extended systems of equations for steady-state, fully developed, lamina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
153
2
1

Year Published

1988
1988
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(175 citation statements)
references
References 24 publications
19
153
2
1
Order By: Relevance
“…We note that the critical Taylor numbers T c found here are consistent with the results of Winters [38], who solved the full equations numerically. Winters also used bifurcation detection and continuation methods to follow the solution branches as the parameters were changed, and the results of Kachoyan [28] agree qualitatively with the numerical work of Winters.…”
Section: Oddsupporting
confidence: 89%
See 2 more Smart Citations
“…We note that the critical Taylor numbers T c found here are consistent with the results of Winters [38], who solved the full equations numerically. Winters also used bifurcation detection and continuation methods to follow the solution branches as the parameters were changed, and the results of Kachoyan [28] agree qualitatively with the numerical work of Winters.…”
Section: Oddsupporting
confidence: 89%
“…This type of flow is intended to model flow in curved rectangular pipes, and flow in helically coiled ducts with small pitch. Recent numerical and experimental work on this problem has been carried out by, for example, Winters [38], Hille et al [25], Joseph et al [27], Ghia and Sokhey [21], De Vriend [18] and Cheng et al [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although all the solution branches in Fig. 2 have been already found by, for example, Winters, 4 Wang and Yang, 9 and Mondal et al, 5 they are newly calculated for the present study.…”
Section: A Summary Of 2d Solutionsmentioning
confidence: 57%
“…Numerical and experimental investigations 4,5 have shown that many types of steady and unsteady solutions appear as the Dean number, Dn, increases for the curved-rectangular-duct flow, where Dn is proportional to the Reynolds number multiplied by the square root of the duct curvature. If Dn is very small, a steady solution, which has two secondary vortices ͑two-vortex solution͒ in a cross section, is realized in not only the numerical simulations but the experimental observations.…”
Section: Introductionmentioning
confidence: 99%